Comment l’exemple des cimetières-jardins interprète la mémoire funéraire québécoise - Manon Cornellier (Conserveries Mémorielles)
Garden cemeteries are great sites for the observation of different treatments of funerary memory throughout history. They belong to a transition period in the history of remembering the dead, between the urban cemeteries of the 16th-18th centuries and the contemporary cemetery parks and were at the junction of a management by factories and a support from private companies that offered funeral goods and services in a "all-in-one" formula. The "industrialization of death" was slowly taking place, as tombstones were carved by professional sculptors, the iconography became more diversified and developed, new materials were becoming the norm and private companies specialized in funerals opened their doors. The monuments in garden cemeteries thus account for a standardization of certain burial practices. Having had their heyday in the first quarter of the twentieth century, the popularity of garden cemeteries waned afterwards. This text attempts to show how these cemeteries were places of commemoration for both short-term and long-term memory and why they have become, in many cases, places of short-term memory. As a result of a social disengagement towards them, these sites devoted to a long-term memory are somehow marked by forgetfulness and became incidentally actors in a short-term memory.